The use of design as a strategic tool for innovation: an analysis for different firms' networking behaviours - Cesário, Marisa (2019)
Current research indicates that the use of design strategy in companies is related to innovation and leads to competitiveness. This research aims empirically to analyse the relationship between firms' networking behaviours and their propensity to engage in design activities. Although much of the literature on networks focuses on the relationship between the development of external linkages and innovation, we argue that small and medium-sized enterprises' (SMEs)' relationships with different agents and intermediaries, on diverse geographic scales, play an important role for how companies use design as an element of innovation. Using the Community Innovation Survey (CIS 2012) database for Portugal, a logistic regression was performed using the strategic use of design' as a binary dependent variable. We found that firms' engagement in informal relationships with heterogeneous agents, such as public customers, consultants or conference partners, is positively associated with the strategic use of design. The use of firms' internal assets as information sources also proved to be significant. Regarding market relations, the results indicate that a geographic scaling-up contributes to increasing the odds of a firm recognizing the strategic role of design for competitiveness.